Docking-based evaluation against Human Tankyrase-1 and Tankyrase-2 enzyme. (2022) - Garg, Aakriti; Kant, Kamal; Roy, Kuldeep K.; Sahoo, Abhishek; Malakar, Chandi C.; Gupta, Sreya
Graphical abstract: Abstract: The detailed molecular docking studies have been performed to verify the biological activities of the synthesized compounds against the Human Tankyrase 1 and 2 (TNKS-1 and 2) enzymes implicated in the colorectal cancer. The presented in-silico studies have revealed that some of the synthesized derivatives exhibits better binding affinity compared to the existing clinical candidate drug XAV939, and thus demonstrated the novel scaffolds for further exploration towards targeting TNKS-1 and 2 inhibition. The information obtained from in-silico studies might be very useful to identify the novel lead compounds for further development towards the treatment of colorectal cancer targeting TNKS-1 and 2inhibitions. However, the finding requires the experimental validation by in vitro and in vivo investigations to develop effective drug for TNKS-1 and 2 inhibitions.